Efektifitas bahan ajar interaktif bermuatan nilai karakter dalam pendekatan saintifik terhadap pencapaian kompetensi peserta didik Kelas XI SMA Pembangunan Laboratorium UNP - Elsa Rahmayuni; Murtiani Murtiani; Amali Putra; Yenni Darvina (PILLAR OF PHYSICS EDUCATION, 2019)
Achievement of student competencies in learning physics is still relatively low. The results of the distribution of questionnaires in the UNP Laboratory Development High School showed that teaching materials and learning approaches used in the learning process were less varied so that they were unable to provide adequate competency achievement for students. The teaching material used in the study is interactive teaching material with character values in a scientific approach developed by Haflianita Hasanah (2018) which has been tested as valid and practical. As for the effectiveness of teaching materials has not been done. The purpose of this study is to examine the effectiveness of Interactive Teaching Materials Loaded with Character Values in Scientific Approaches to Wave Material and Optics Towards Increased Competence of Class XI Students in the UNP Laboratory Development Laboratory.The type of research used is Pre-experimental Designs with One-Group Pretest-posttest. The sample in this study was class XI MIA 2 with a total of 30 students, taken by purposive sampling technique. Data collection tools in the form of pre-test and post-test written tests for knowledge competencies, observation sheets for attitude competencies, scoring rubrics for skills competencies. Analysis of the effectiveness test was performed using a correlated t test. After conducting research and continuing with analyzing data, it can be concluded that Interactive Teaching Materials with Character Values in Scientific Approaches on Wave Material and Optics are effectively used in learning at a real level of 0.05 which can be seen from an increase in students' learning competency in the aspect of knowledge at the time after using Interactive Teaching Materials. The results of the effectiveness based on the calculated value obtained is smaller than the value of the table. The t value obtained is -31.12 while the value of -table is equal to -1.701.